Celebrity Endorsement and Brand Image Synergy: The Role of Brand Awareness in Driving Buying Decision for Scarlett Products - Toresa, Dedeh Cahyani; Yuswono, Irawan (PT. Hafasy Dwi Nawasena, 2025)
This study aims to analyze the influence of celebrity endorsement and brand image on purchasing decisions, with brand awareness as a mediating variable among Scarlett product consumers in Kendari City. A quantitative approach was employed using a survey method for data collection. Data from 240 respondents were obtained through an online questionnaire and analyzed using Structural Equation Modeling (SEM) with AMOS software. The results indicate that both celebrity endorsement and brand image significantly affect brand awareness and purchasing decisions. Furthermore, brand awareness mediates the relationship between celebrity endorsement, brand image, and purchasing decisions. These findings align with the Consumer Culture Theory (CCT), which emphasizes that consumer decisions are influenced not only by functional aspects but also by symbolic and social meanings attached to brands. The practical implications of this research suggest that companies should integrate strong branding strategies with carefully selected celebrity endorsers to enhance consumer visibility and trust. This study also contributes theoretically to the development of consumer behavior models based on cultural symbolism, especially within the context of local brands in the digital era